Designações espaciais em letras de canções gauchescas : construção de sentido no processo de leitura - Santos, Odair José Silva dos (My University, 2018)
Gauchesque (or gaucho) culture has close links with the geographic formation of the state of Rio Grande do Sul (RS) and this is represented, for example, in gauchesque songs, when geotopological forms (such as relief, vegetation and hydrography) are mentioned to refer to the state as a whole. Likewise, geopolitical contours are referred to as cities, as the state itself or its cardinal position in Brazil. The general aim of this thesis is to examine the construction of meanings and interpretations of spatial designators (DE) of lyrics of gaucho songs, as evidenced from the reading of two categories of readers: those related to traditionalist movements and those not related to them. The problem that guides this investigation is: what constructions of meanings and interpretations are revealed in spatial designators related to RS in gaucho song lyrics, as observed in certain categories of readers? This thesis deals with the idea of reading as interpretation, based on Cognitive Linguistics to reflect on how individuals interpret different words in regional songs, when arranged in different statements, using data from researches by Barcelona (2003), Evans (2009), Fillmore (2009), Geeraerts (2009), Panther and Thornburg (2007), Panther (2006), Silva (2010), Taylor (2009) and Teixeira (2001). In order to achieve it main goal, the investigation includes research on the history of gaucho musicography (in order to contextualize, select and justify the set of songs used), lexicographic research (in order to check how the meanings of designators are registered in dictionaries), field research (by means of a questionnaire and interviews, in order to analyze how the informants-readers interpret the words), introspective analysis (from the perspective of the researcher) and analysis of the answers to the questionnaire and interviews. This set of researches and analyses has evidenced that DEs are seen, mostly, as metonymic processes in which the PARTS of the state of RS represent the WHOLE. In addition, as an answer to the question of this investigation, the individuals related to traditionalist movements have shown greater sensitivity in their interpretations, assigning DEs more details and traces of affection, while those in the category not related to traditionalist movements tended to construct broader generic meanings.
A cultura gauchesca tem vínculos estreitos com a formação geográfica do Estado do Rio Grande do Sul (RS) e isso é representado, por exemplo, em canções gauchescas, quando as formas geotopológicas (relevo, vegetação e hidrografia) são mencionadas para referir ao estado como um todo. Da mesma forma, os recortes geopolíticos são referidos pela menção a cidades, ao próprio RS ou à sua posição cardeal em relação ao Brasil. Nesse âmbito, o objetivo geral desta tese é examinar as construções de sentidos e interpretações de designadores espaciais (DE) de letras de canções gauchescas, a partir da leitura por parte de duas categorias de leitores: os vinculados a movimentos tradicionalistas e os não vinculados a esses movimentos. O problema que guia esta pesquisa é: que construções de sentidos e interpretações são revelados nas designações espaciais relativas ao RS nas letras de canções gaúchas, verificadas por meio da leitura de certas categorias de público receptor? Trabalhamos, então, com a ideia de leitura como interpretação, buscando subsídios na Linguística Cognitiva para refletir sobre como indivíduos interpretam vocábulos diferentes em canções regionais, quando dispostos em enunciados diferentes, com base nas pesquisas de Barcelona (2003), Evans (2009), Fillmore (2009), Geeraerts (2009), Panther e Thornburg (2007), Panther (2006), Silva (2010), Taylor (2009; 2010) e Teixeira (2001).Para a consecução de nosso objetivo geral, esta investigação é construída por uma pesquisa sobre a história da musicografia gauchesca (para contextualizar, selecionar e justificar o conjunto de canções utilizadas), pesquisa lexicográfica (para verificar como os sentidos dos designadores são registrados nos dicionários), pesquisa de campo (por meio de questionário e entrevistas, para levantar como os informantes-leitores interpretam os vocábulos), análise introspectiva (na perspectiva do pesquisador) e análise das respostas do questionário e das entrevistas. A partir desse conjunto de pesquisas e análises, constatamos que os DEs são interpretados, em grande parte, como processos metonímicos em que as PARTES do RS representam o TODO. Respondendo à questão de pesquisa, a categoria de sujeitos ligados a movimentos tradicionalistas demonstrou maior sensibilidade em suas interpretações, conferindo aos DEs pormenores e traços de afetividade, enquanto a categoria não vinculada a esses movimentos apresentou uma tendência a construir sentidos mais genéricos.
Keywords: Música tradicional sul-rio-grandense; Leitura; Compreensão na leitura; Music south-rio-grandense; Reading; Reading comprehension